Salivary Proteome Profile of Xerostomic Patients Reveals Pathway Dysregulation Related to Neurodegenerative Diseases: A Pilot Study - Henry, Abhijeet A.; Beckman, Micaela F.; Fry, Thomas S.; Brennan, Michael T.; Bahrani Mougeot, Farah; Mougeot, Jean-Luc C. (International journal of molecular sciences, 2025)
Xerostomia, the subjective complaint of a dry mouth, is frequently associated with salivary flow reduction and/or salivary gland hypofunction. This condition significantly impacts an individual’s quality of life and oral health, including difficulties in speaking, chewing, and swallowing. Xerostomia may be caused by autoimmune diseases, xerogenic medications, and radiation therapy. Our objective was to identify differentially expressed proteins in the saliva of patients with medication and autoimmune disease-associated xerostomia compared to non-xerostomic control subjects. Two groups of individuals (N = 45 total) were recruited: non-xerostomic subjects (NX-group; n = 18) and xerostomic patients (XP-group; n = 27). Dried saliva spot samples were collected from major salivary glands, i.e., parotid (left and right) and submandibular glands. Proteomic analysis was performed by deep nanoLC-MS/MS. Differential protein expression in the XP-group relative to the NX-group was determined by the Mann–Whitney U-test with FDR Benjamini–Hochberg correction (padj < 0.05). The Search Tool for Recurring Instances of Neighboring Genes (STRINGv12.0) was used to generate interaction networks and perform pathway analysis. A total of 1407 proteins were detected. Of these, 86 from the left parotid gland, 112 from the right parotid gland, and 73 from the submandibular gland were differentially expressed proteins (DEPs). Using STRING analysis, we identified, for the first time, several neurodegenerative disease-associated networks, primarily involving the downregulation of the 20S proteasome core complex and glyoxalase proteins across salivary glands. In this study, we determined neuronal dysregulation and impaired methylglyoxal (MGO) detoxification, possibly through reduced protein expression of glyoxalase Parkinson’s Disease (PD) Protein 7 (encoded by the PARK7 gene) in major salivary glands of xerostomic patients. Indeed, impaired MGO detoxification has been previously shown to cause salivary gland dysfunction in a mouse model of type 2 diabetes. Based on other DEPs associated with neurodegenerative disorders, our results also suggest a possible deficiency in the parasympathetic nervous system innervation of salivary glands, warranting further investigation.